The European financial and economic crisis: alternative solutions from a (post-) keynesian perspective - Hein, Eckhard; Truger, Achim; van Treeck, Till (Düsseldorf, 2011)
"The financial and economic crisis in the Euro area has revealed a number of important flaws in the economic policy framework in Europe. On the one hand, the imbalances, which have dominated European development since the introduction of the euro, are not sustainable; and this is more serious in a period of crisis in particular. On the other hand, it has become clear that the Euro area suffers from a serious lack of institutions and policy concepts, which will not allow coping with deep financial and economic crises unless a deep restructuring takes place. The policy reactions of European governments, the European Commission and the European Central Bank in cooperation with the IMF will, therefore, hardly be able to initiate recovery. On the one hand, some important steps towards financial stabilisation have been made. On the other hand, however, these are combined with restrictive fiscal and wage policies, which will impose deflationary pressure on major parts of the Euro area and thus prevent stabilisation (or reduction) of public debt-GDP ratios. In the paper we will first analyse the imbalances, which have been built up in the Euro area, before we briefly review the policy responses towards the crisis. Since the prescribed fiscal and wage policies are still dominated by the New Consensus Macroeconomics theoretical framework, we will then develop an alternative macroeconomic policy model based on Keynesian and Post-Keynesian principles. It will be shown that stabilising wage and active fiscal policies will have major roles to play in order to cope with the imbalances and to initiate recovery for the EU as a whole. Furthermore, current account targets will have to be included into intra-Euro area policy coordination."